CNOT6L regulates energy metabolism in the ovarian granulosa cells associated with polycystic ovary syndrome - Han, Shan; Xie, Yanqiu; Lv, Jiale; Sun, Xuedong; Shi, Yuhua (Frontiers in Cell and Developmental Biology, 2025)
The endocrine functions exerted by ovarian granulosa cells (GCs) are crucial factors in maintaining follicle development, as oocyte development relies on providing energy substrates and cytokines by ovarian granulosa cells. The mRNA deadenylase level of granulosa cells precisely regulates the follicular development processes. In this study, we detect the expression level of the deadenylase CNOT6L in polycystic ovarian syndrome (PCOS) patients’ granulosa cells and mouse models’ ovaries. The results found that the CNOT6L significantly upregulated in the ovarian granulosa cells of both PCOS patients and mouse models. Subsequently, we conducted the Cnot6l-overexpressed granulosa cells to explore the alterations by which CNOT6L regulates ovarian granulosa cell function. The overexpression of CNOT6L in granulosa cells significantly inhibited the glycolytic pathway, activated the mitochondrial oxidative phosphorylation pathway, led to a reduction in the generation of the intermediate product lactate, and resulted in impaired energy supply to the oocyte. Subsequently, we performed Full-length transcriptome sequencing on the granulosa cells and investigated the impact of mRNA poly(A) level differences on granulosa cell dysfunction in PCOS. This study offers new insights into the role of CNOT6L in regulating energy metabolism homeostasis and its involvement in follicular developmental disorders related to polycystic ovary syndrome.